Configuring node status in a two-phase tightly integrated mode for wireless sensor networks. (14th February 2007) - Tian, Di; Lei, Zhijun; Georganas, N.D.
In wireless sensor networks, one of the main design challenges is to save severely constrained energy resources and obtain a long system lifetime. Low cost of sensors enables us to initially deploy a large number of sensor nodes in a very high density. A potential approach to solve a lifetime problem is to schedule sensor nodes work alternatively by configuring some of them a low-energy, off-duty status. In a single wireless sensor network, sensors assume two main functionalities: sensing and communication. Most of the previous work addressed only one kind of redundancy: sensing or communication alone. In this paper, we prove: "the communication range is twice the sensing range" is the sufficient condition and the tight lower bound to ensure that complete coverage preservation implies connectivity among active nodes, if the original network topology (consisting of all the deployed nodes) is connected. This conclusion enables configuring node status in a two-phase tightly integrated mode. The experimental results show that it leads to more off-duty nodes in double domains than other two strategies.